A interdisciplinaridade e os aspectos conceituais e de representação : análise da área "multidisciplinar" da Tabela de Áreas do Conhecimento em uso pela CAPES - Silva, Roberta Pereira da (2008)
The increasing development of science gave rise to the process of specialization of knowledge originating disciplinary fragmentations in research and teaching activities. In this direction, the interdisciplinarity appears as a movement to integrate different areas of specialization in the creation of new knowledge. This present work investigated interdisciplinary knowledge through conceptual aspects and principles of information representation. The theoretical approach was structured in two main streams : historical and conceptual aspects of interdisciplinarity, and the organization and representation of knowledge aiming to identify elements of classification and modes of formation of subjects. The empirical data analysed was the classification of multidisciplinary areas of knowledge in use by CAPES. The results obtained indicated that the definitions of interdisciplinary in the literature is ambiguous. The empirical data revealed three different approaches to interdisciplinarity: a match of different areas of knowledge, a match of different competences in researchers, and the different factors towards environment of human being as individuals and society. The work also revealed that the theory of classification in the context of Information Science gave important and valid support to the identification and representation of interdisciplinarity.